The Decision to Zakah: The Interacting Roles of Transparency, Service Quality, and Trust - Ruslan, Andi; Widyawati, Widyawati; Hamzah, Aksi (Jurnal Minds: Manajemen Ide dan Inspirasi, 2022)
This study aims to examine the effect of transparency and service quality on the decision of muzakki to use the services of a Zakah Management Organization (OPZ) mediated by trust. This research was conducted for six months on 180 Zakah payers at OPZ in Makassar. The survey data were analyzed by structural equation modeling using AMOS. The results showed that muzakki's trust in Zakah management organizations could mediate the relationship between transparency and service quality on muzakki's decisions to use OPZ services in Makassar. This study contributes to the literature on transparency and service quality in increasing the trust and decision of muzakki in using OPZ services in Zakah distribution.